Usefulness of anterior segment optical coherence tomography in descemet’s membrane detachment following cataract surgery - Lathika, Vasu Kamaladevi; Thresika, Uvaraj; Nayana, Sebastian (International Journal of Research in Medical Sciences, 2017)
Background: Postoperative descemet’s membrane detachments (DMD) can be vision threatening if not detected early and managed appropriately Eyes with DMD usually have corneal haze which may hamper slitlamp evaluation. Anterior segment optical coherence tomography (ASOCT) is a precise, non-invasive imaging technique that yields high resolution cross sectional images of the cornea. This study aims to evaluate the usefulness of AS OCT as compared to slitlamp biomicroscopy in the detection and management of post-operative DMD following small incision cataract surgery. Methods: It was a prospective study on sixty-seven patients who underwent cataract surgery. Slitlamp biomicroscopy and ASOCT were done in all patients on postoperative day one. The presence of descemet’s membrane detachment was noted using each technique. Eyes with DMD were followed up one week and again one month later. ASOCT was repeated to assess the status of DMD. Management was planned accordingly Results: On post-operative day one, only 1.49% of the study group showed descemet’s detachment on slitlamp biomicroscopy, as against 20.89% using ASOCT. This increase in diagnostic yield on ASOCT was statistically significant(p=0.05). On follow-up, descemet’s membrane had reattached in seven eyes one week after surgery and in all eyes one month after surgery, with medical management alone. Conclusions: AS OCT has a definite advantage over slit lamp biomicroscopy in the detection of descemet’s membrane detachment following cataract surgery. Our study also validates the fact that AS OCT helps in follow up and decision making in the management of DMD.